The effect of bioactivation on the biochemical composition and amylolytic activity of hulles oats - E. N. Shabolkina; S. N. Shevchenko; N. V. Anisimkina (Зерновое хозяйство России, 2022)
Hulles oats is a promising grain crop for germination (bioactivation), that is, it is both a technological additive and a functional ingredient that influences the biological value and consumer properties of a new product. The purpose of the current work was to identify the biochemical composition of hulles oats after the bioactivation process and to estimate the state of the carbohydrate-amylase complex of grain. The study was carried out at the experimental plots of the Samarsky Research Institute of Agriculture named after N.M. Tulaykov during 2018–2021. There were studied such oat varieties as the hulled variety ‘Konkur’, the hulles varieties ‘Baget’ and ‘Bekas’. In the long-term trials there was established the high nutritional value of the hulles oat varieties ‘Baget’ and ‘Bekas’ with on 4.5–4.8% of protein, 33.0% of starch and 27.0–39.0% of oil more than these of the hulled variety ‘Konkur’, which indicated great prospects in baking, possibilities of using this crop in the production of starch and oil. The period of bioactivation has shown that 80% of hulles variety seeds demonstrated more active and friendly kernel sprouting, growth and development up to 1.5 mm. There has been experimentally established that the conditions created during germination (water, temperature, air) reduced mass fraction of protein in kernels on 5.4 – 8.8%, starch content in kernels on 19.5–22.9%, oil in kernels on 5.1 – 7.0% compared with non-sprouted oats. Due to more active germination of hulles oats, the consumption of protein, polysaccharides and oil by the kernels of the varieties ‘Baget’ and ‘Bekas’ was on 2.3–3.4% more active. There has been estimated the state of carbohydrate-amylase complex. The kernels of hulles oats in contrast to hulled oats were characterized by lower amylolytic activity (880–890 u.a. of viscosity on the Brabender amylograph and 348–354 c of ‘falling number’ according to Hagberg-Perten). Bioactivation of grain greatly increased the amylolytic activity: the maximum viscosity of the suspension in the varieties Baget and Bekas stopped at the level of 105 AU, the falling number was 75 s. The total enzymatic activity of amylases has increased in absolute terms on 13.3 – 43.4 mg, the dextrinating activity of α-amylase increased in 2.2–9.8 times, and the saccharifying effect of β-amylase increased in 1.7–3.9 times. The hulles oats, having low amylolytic activity, in the process of bioactivation has acquired greater manufacturability and functionality as an ingredient that influences the biological value of a new product.